(untitled) (Orfeu, 2019)
In a partial perspective, this is a report about experiments that aimed to produce the synthesis of sounds similar to a Brazilian folk guitar, using variations of the Karplus-Strong method. Delay-lines implementing the waveguide model are the basis of this sound synthesis method. Therefore, this study belongs to the field of physical modelling. The departing point of the developed variants were the algorithms of Lazzarini et al. (2016) e Mikelson (2000). In a broader perspective, this study searches to incorporate to the model other characteristics of the acoustic instrument, as the double strings strikes, modal components, formants and the resonance of the instrument’s body. The resulting hybrid algorithm incorporated a variety of other methods, as the synthesis by sum of sine waves plus noise of Serra (1997) and the FOF technique described by Clarke (2000). The research of Paiva (2017) provided experimental values used in the model parametrization. The results were used to compose the piece Bestiário III for guitar and electronic sounds generated after the viola caipira model. The pitch matrix and the proportions of the complex rhythms were loosely inspired by Paiva’s (2017) spectral analysis of the viola caipira.